Ordered array of pores on a polymer film - Fong, Yik Ling. (2009)
This project examines the arrays formed on various glass substrates using polymer solutions via the breath figure technique and were compared to find out whether a difference in number of carboxy group, weight % and substrate surface plays a part and how each variable alters the size and order of the pores.